#TITLE_ALTERNATIVE# - FITRIANI (12808034); Pembimbing : Dr. Tri Wahyu Hadi, RACHMY
Relationships between Cloud-to-ground (CG) lightning activity and convective clouds over Indonesian regions have been studied in the past but detailed studies at local scale are still very limited. The availability of ground based lightning observation system has made it possible for us to carry out a local scale analysis of the CG lightning activities. However, continuous observations of convective activities are more difficult to perform except by utilizing satellite imagery. Hence, the main purpose of this study is to investigate the suitability of convective index derived from MTSAT (Multi-Functional Transport Satelitte) infrared (IR1) satellite imagery to characterize cloud convection types that are strongly correlated to CG lightning both temporally and spatially. It is found that comparison between data obtained from lightning detector installed in Bandung, West Java, and the convective index derived from satellite imagery can provide acceptable pattern of relationships between CG lightning and cloud convections. However, it is of interest to note that the strongest CG lightning occurs during the period of land-sea contrast of diurnal convection indicating relatively stronger updrafts in the convective clouds. Additionally, negative and positive CGs are found to have similar phases during inland convections but hey occurs with noticeable time lags for convections over sea. In this case study, an ambiguous time stamping were found in the lightning data but analysis has been performed based on shifted time series. More accurate data from a lightning detection network are necessary for future studies.